Liver Fibrosis and MAFLD: From Molecular Aspects to Novel Pharmacological Strategies - Qu, Weiyi; Ma, Tengfei; Cai, Jingjing; Zhang, Xiaojing; Zhang, Peng; She, Zhigang; Wan, Feng; Li, Hongliang (Frontiers in Medicine, 2021)
Metabolic-associated fatty liver disease (MAFLD) is a new disease definition, and this nomenclature MAFLD was proposed to renovate its former name, nonalcoholic fatty liver disease (NAFLD). MAFLD/NAFLD have shared and predominate causes from nutrition overload to persistent liver damage and eventually lead to the development of liver fibrosis and cirrhosis. Unfortunately, there is an absence of effective treatments to reverse MAFLD/NAFLD-associated fibrosis. Due to the significant burden of MAFLD/NAFLD and its complications, there are active investigations on the development of novel targets and pharmacotherapeutics for treating this disease. In this review, we cover recent discoveries in new targets and molecules for antifibrotic treatment, which target pathways intertwined with the fibrogenesis process, including lipid metabolism, inflammation, cell apoptosis, oxidative stress and extracellular matrix formation. Although marked advances have been made in the development of antifibrotic therapeutics, none of the treatments have achieved the endpoints evaluated by liver biopsy or without significant side effects in a large-scale trial. In addition to the discovery of new druggable targets and pharmacotherapeutics, personalized medication and combinatorial therapies targeting multiple profibrotic pathways could be promising in achieving successful antifibrotic interventions in patients with MAFLD/NAFLD.